HUBUNGAN PENGAWASAN ORANG TUA DAN MEDIA INFORMASI TERHADAP PERILAKU SEKSUAL PRANIKAH PADA REMAJA - B Hamzah; St. Rahmawati Hamzah (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2020)
Background: Premarital sexual behavior is one of the result of promiscuity. This problem tends to be carried out by middle adolescent groups (15-18 years). Around 63% of junior high school, high school and university-age adolescents in Indonesia claimed to have had premarital sex. Some permissive dating behaviors performed by adolescents include holding hands when dating (92%), kissing (82%), and petting (63%). Purpose: This purpose ostudy aims to determine the relationship of parental supervision and information media with premarital sexual behavior in adolescents at State High School No 1 Kotamobagu. Method: This study applied an analytic cross-sectional design with a sample of 299 school-age adolescents aged 14-18 years. The sampling technique used was stratified random sampling. Data were collected by direct interviews with respondents and analyzed univariately and bivariately using the chi square test. Results: The results of the study based on the chi square test showed that there was a relationship between parental supervision (p=0.006) and information media (p=0.001) with premarital sexual behavior in adolescents. Conclusion: There was a relationship between parental supervision and information media with sexual behavior in adolescents at State High School No 1 Kotamobagu. It is recommended to the relevant parties to play an active role in conducting supervision and providing sexual education early on so that students avoid premarital sexual behavior.Keywords: Information Media; Parental Supervision; Premarital Sexual Behavior